2016
DOI: 10.1111/age.12402
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide association study of copy number variations with umbilical hernia in swine

Abstract: Umbilical hernia (UH) is one of the most common congenital defects in pigs, leading to considerable economic loss and serious animal welfare problems. To test whether copy number variations (CNVs) contribute to pig UH, we performed a case-control genome-wide CNV association study on 905 pigs from the Duroc, Landrace and Yorkshire breeds using the Porcine SNP60 BeadChip and penncnv algorithm. We first constructed a genomic map comprising 6193 CNVs that pertain to 737 CNV regions. Then, we identified eight CNVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 39 publications
2
32
0
1
Order By: Relevance
“…Moreover, SNPs within the NUAK1 gene showed associations with only French Landrace but not with more pigs and it may be caused by the limited sample numbers. For the remaining three SNPs, the comparison in mixed or purebred groups did not uncover notable differences between inguinal/scrotal hernias and the polymorphisms of DEGS1, COL2A1 and MMP2 (p > 0.05) providing some evidence that numerous SNPs in pig inguinal/scrotal hernias were likely breed specific, which coincided with the former studies of pig inguinal/scrotal hernias [29][30][31].…”
Section: Confirmation Of Association Results In 270 Samplessupporting
confidence: 77%
“…Moreover, SNPs within the NUAK1 gene showed associations with only French Landrace but not with more pigs and it may be caused by the limited sample numbers. For the remaining three SNPs, the comparison in mixed or purebred groups did not uncover notable differences between inguinal/scrotal hernias and the polymorphisms of DEGS1, COL2A1 and MMP2 (p > 0.05) providing some evidence that numerous SNPs in pig inguinal/scrotal hernias were likely breed specific, which coincided with the former studies of pig inguinal/scrotal hernias [29][30][31].…”
Section: Confirmation Of Association Results In 270 Samplessupporting
confidence: 77%
“…Associations between CNVs and phenotypic performance have been documented in a whole multitude of species including dairy cattle [6], beef cattle [7,8], chickens [14], dogs [15], pigs [16] and humans [17][18][19]; thus CNVs are likely to contribute to some of the underlying genetic variability. The ability to estimate the genomic or phenotypic merit of individuals based on CNVs requires knowledge of the CNV genotypes of those animals.…”
Section: Discussionmentioning
confidence: 99%
“…Several quantitative trait loci (QTL) associated with UH have already been reported for pigs. In a search in the pig QTLdb (https://www.animalgenome.org/cgi-bin/QTLdb/SS/index -11/02/2019), 54 QTLs for umbilical hernia have been found in several pig breeds, being located in chromosomes SSC1, SSC2, SSC3, SSC4, SSC6, SSC7, SSC8, SSC9, SSC10, SSC11, SSC13, SSC14, SSC15, SSC16 and SSC17 [11][12][13][14]. Ding et al (2009) [11] performed the first genomic study with UH and found some chromosomic regions related to the appearance of this condition.…”
Section: Introductionmentioning
confidence: 99%